THE QUESTION OF THE CONJUNCTION "WITH" IN UZBEK LINGUISTICS - Z. D. Mirzakarimowa; M. N. Kasimowa (Scholars Digest Publishing, 2023)
In this article, the conjunction with is in Uzbek as well as in Turkic languages. The auxiliary in also a connecting link, cases were analyzed.
Keywords: organized group, connecting link, informatics connotation, counterparty, component, denotative, semantics.